Plant Antimicrobial Compounds and Their Mechanisms of Action on Spoilage and Pathogenic Bacteria: A Bibliometric Study and Literature Review - Jesús Guadalupe Pérez-Flores; Laura García-Curiel; Emmanuel Pérez-Escalante; Elizabeth Contreras-López; Guadalupe Yoselín Aguilar-Lira; Carlos Ángel-Jijón; Luis Guillermo González-Olivares; Elena Saraí Baena-Santillán; Israel Oswaldo Ocampo-Salinas; José Antonio Guerrero-Solano; Lizbeth Anahí Portillo-Torres (Applied Sciences)
This research explored the potential of plant antimicrobial compounds as natural alternatives to synthetic antimicrobials in the food and pharmaceutical industries, emphasizing the urgent need to combat antimicrobial resistance. It detailed various mechanisms by which these plant-derived compounds inhibit microbial growth, including disrupting cell membrane integrity, impeding cell wall and protein synthesis, and preventing biofilm formation, ultimately leading to bacterial cell death. This study highlighted the specific effects of plant antimicrobials on bacterial cells, such as inhibiting biofilm formation, cellular respiration, and cell motility, while also modulating oxygen consumption and reactive oxygen species generation, which are vital in addressing biofilm-mediated infections. Additionally, these compounds can regulate the expression of virulence factors and efflux pumps, enhancing antibiotic efficacy. A bibliometric analysis revealed a growing trend in research output and international collaboration, particularly from China and the United States, with key journals including “Frontiers in Microbiology” and “Antimicrobial Agents and Chemotherapy.” The analysis identified six clusters related to plant antimicrobial research, underscoring the need for further investigation into the mechanisms and applications of these bioactive compounds. In conclusion, understanding the action of plant antimicrobials is important for their effective application in combating antimicrobial resistance.